The value of the written monument of Tonykok (Herald of Journalism, 2020)
This article discusses the assistance of Kagan counselor wise Tonykok and the kagan Yelteris-Kutlug Khan of the Turkic khanate in the drafting of decrees and other written documents of Turkic Empire, his participation  in the battles. There pointed out the personal records of Tonykok of those times and their differences from the paintings on the rocks.Educated in China, Tonykok created many of his works in poetry and philosophy. The influence of the teachings of the Tao can be traced in the written monuments of Tonykok. Considered these historical written monu- ments one can confidently speak of their poetic heritage. Here you can see the contribution of the Khagan Yelteris-Kutlug Khan and Tunykok in the development of the written language of the Turkic Khaganate.
Keywords: Turkic kһaganate, runa, Рһilosoрһical tһougһts, typology.